Drying of mango slices with heated air - Maryanto; Jindal, Vinod Kumar; Illangantileke, Sarath G.; Gupta, Chandra P.; ASEAN, USAID (Bangkok : Asian Institute of Technology, 1986)
Drying characteristics of mango slices were studied in a cabinet dryer using heated air. The effect of predrying treatments was also investigated to obtain the final product of superior quality. Experimental conditions included three air temperatures of 50,60 and 70C̕ three slice thicknesses of 0.5, 1.0 and 1.5 cm and four tray loadings of 1.225, 2.45, 3.675 and 4.9 kg/m2, respectively, Four predrying treatments consisted of dipping the mango slices in solutions of 1.5% sodium metabisulphite, 1.5% potassium metabisulphite followed dipping in 0.4% calcium chloride, steam blanching and no treatment serving as control. The relative humidity of the air was not controlled. The ambient air temperature and humidity during drying ex0periments were in range of 28-32C and 80-85%, respectively. A simple logarithmic model described the drying results adequately. The drying constant depended upon the air temperature, slice thickness and material loading. The dried mango slices appeared to be of good color when treated with sulphite solutions at all drying temperatures. Drying air temperature had a more influence on the texture of mango slices irrespective of the predrying treatment. There were strong correlations between subjective and instrumental measurements of the quality attributes of dried mango slices. The loss in vitamin C was more influenced by the predrying treatment than air temperature. In general, sulphite treatment resulted in least loss of vitamin C due to drying.
A research study submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Environment, Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 1986
Keywords: Mango; Fruit -- Drying